Analisis Risiko Ergonomi Aktivitas Menenun pada Perajin Tenun Tradisional Kepulauan Riau : Ergonomic Risk Analysis of Weaving Activities among Traditional Weavers in the Riau Islands - Yosia Tambunan; Abdul Alimul Karim; Meylia Vivi Putri; Dion Dwi Adhita; Jonathan Adi Nugraha; Dwi Cahya Rada (Fakultas Rekayasa dan Teknologi Industri, 2026)
Weaving activities at the Dekranasda Building in the Riau Islands represent a traditional occupation that continues to hold cultural significance. This activity is performed manually using non-mechanized looms, requiring precision, hand-foot coordination, and prolonged sitting. Such conditions may lead to musculoskeletal complaints in the neck, back, shoulders, arms, and legs, affecting workers’ comfort, health, and productivity. This study aims to identify musculoskeletal complaints among weaving artisans and assess the postural risk during yarn setup and weaving activities. A descriptive quantitative approach with observational methods was employed. Data were collected through the Nordic Body Map (NBM) questionnaire to measure body discomfort, photographic documentation of working postures, and postural analysis using the Rapid Entire Body Assessment (REBA) method. NBM results indicated that the most frequently reported discomfort occurred in the wrists, ankles, back, and shoulders. REBA analysis showed a score of 9 for yarn setup and 8 for weaving activities, both classified as high risk, indicating a need for ergonomic interventions. Discussion highlighted that prolonged sitting, repetitive arm movements, and forward-leaning postures increase the risk of musculoskeletal complaints. Ergonomic improvements, such as adjusting table height, seat position, hand reach, and providing work breaks, are recommended to reduce these risks. Future research is suggested to perform detailed anthropometric measurements of the artisans to design more suitable workstations and evaluate the effectiveness of ergonomic improvements in reducing musculoskeletal complaints and REBA scores.